The effect of hydroalcoholic extract of Otostegia persica (Burm.) Boiss. against H2O2-induced oxidative stress in human endothelial cells - L. Safaeian; S. Yaghoobi; S.H. Javanmard; N. Ghasemi-Dehkordi (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Otostegia persica (Burm.) Boiss. is an endemic plant of Iran with various applications in traditional medicine which contains of several antioxidant constituents. This research was aimed to investigate the effect of hydroalcoholic extract from O. persica aerial parts in human umbilical vein endothelial cells (HUVECs) using hydrogen peroxide (H2O2) as an inducer of oxidative damage. Methods: The total phenolics content of the extract was estimated using Folin-Ciocalteu method. The probable cytotoxicity of O. persica extract and also its cytoprotective effect on HUVEC cells against oxidative stress was assessed using 3-(4,5- Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The intra and extra-cellular hydroperoxides concentration and ferric reducing antioxidant power (FRAP) were determined in pretreated cells. Results: Total phenolics content was found to be 42.41±0.1 mg tanic acid equivalent/g of thedried extract. No cytotoxic effect was observed from O. persica extract in the range of 25-250 µg/mL. Pretreatment of HUVECs with O. persica extract with the concentrations of 50-250 µg/mL significantly reduced the cytotoxic effect of H2O2. Otostegia persica extract attenuated the concentration of hydroperoxides and increased FRAP value in intra- and extra-cellular fluids at different concentration ranges. Conclusion: This study indicated the antioxidant and cytoprotective activities of O. persica extract against H2O2-induced oxidative stress in HUVEC cells; however, more researches are required for finding the precise mechanism and assessing its clinical value.